Positive Parenting from the Perspective of Luqman Al-Hakim - Rahmatullah, Azam Syukur; Marpuah, Siti (Jurnal Pendidikan Agama Islam, 2022)
Purpose–This study aims to exlpore more deeply the positive parenting based on QS Luqman verses 13-19, which discusses parenting by Luqman and is made an exemplary role model of "positive parenting" by Allah SWT. It is so that parenting is created oriented towards the Qur'an and does not deviate from the "standard rules" of parenting based on the Qur'an. Hence, it is expected that there will be products for raising children who are illahiyah pious and socially pious. Design/methods/approach–This qualitative research with a content analysis approach explored and discussed the contents of written or printed information in the mass media more deeply. In this case, the researcher searched for articles closely related to parenting issues and about Luqman al-Hakim through Google Scholar. Findings– This study highlights several of Luqman's parenting characteristics that made him intelligent in raising children, i.e., being firm in matters of faith in QS Luqman verses 13 and 17, gentle in speaking in QS Luqman verses 13, 16, and 17, attached to the child (intimacy) in QS Luqman verses 13, 16, 17, 18, and 19, and constantly reminding children to do good in QS Luqman verses 13, 16, 17, 18, and 19. Research implications/limitations–Some of Luqman's parenting styles successfully explored based on QS Luqman, including parenting based on being valued, parenting based on understanding and enlightening, and parenting based on self-control. Originality/value–Research with the theme of positive parenting originated from the verses of the Qur'an about Luqman al-Hakim has not been studied much. Generally, studies only revolve around parenting, ways of educating, and Luqman Hakim's parenting concept. Nevertheless, studies related to positive parenting have not been found. Therefore, research is pure, rich in novelty, and has a positive scientific contribution.